The challenges of modular teaching at Datu Odin Sinsuat North district Maguindanao II Division, Philippines - Lomboy, Lorena Bello; Kadtong, Maeda Langguyuan; Dalgan, Bainera K.; MAT-PE, Candao G. Daglok; MSciEd, Norma Z. Dalgan (Edelweiss Applied Science and Technology, 2025)
The study aimed to identify the problems and challenges faced by educators in Datu Odin Sinsuat, North District, Maguindanao II Division, during the implementation of modular instruction, as well as potential solutions. Employing a descriptive research design, the study utilized a survey questionnaire to gather comprehensive data on the difficulties encountered by teachers when transitioning to modular learning, particularly due to the COVID-19 pandemic. Data analysis involved calculating frequency, percentage, mean, and standard deviation to interpret the responses effectively. The results clearly indicated a wide array of issues faced by teachers during the shift to modular instruction. These included concerns related to the time required for module preparation and distribution, the lack of essential technological devices such as computers, laptops, printers, and copiers, and the absence of parental guidance during the implementation of learning modules. Furthermore, teachers reported insufficient personal protective equipment (PPE) during in-person distribution and retrieval of modules, highlighting safety concerns. Respondents strongly recommended that the Department of Education (DepEd) provide teachers with adequate training in module creation and consider hiring qualified personnel to assist in this process. Additionally, teachers should be provided with comfortable and functional workspaces equipped with reliable internet access. Although the school’s ICT room is designated as the production facility for modules, students should have access to mobile data loads to facilitate communication and information sharing. DepEd schools must also ensure the safety and security of teachers during the distribution and retrieval of modules, especially in the context of health protocols and safety measures.